Assessment of lifestyle modifications among Sudanese individuals with diabetes: The situation so far and the need to do more - Ahmed O Almobarak; Safaa Badi; Wadie M Elmadhoun; Samar B Siddiq; Hanan Tahir; Mugtaba Osman; Sufian K Noor; Mohamed Suliman; Mohamed H Ahmed (Wolters Kluwer Medknow Publications, 2020)
BACKGROUND: Inadequate lifestyle practices among individuals with diabetes may influence the progression of diabetes and its complications. The aim of this study was to assess the lifestyle practices among individuals with diabetes in Sudan. METHODOLOGY: This was a descriptive, cross-sectional, health facility-based study conducted in 3 diabetes centers treating individuals with diabetes. The data were collected using a standardized pretested metabolic questionnaire about lifestyle and were analyzed by performing descriptive and inferential statistics through SPSS program version 23. RESULTS: A total of 528 patients with diabetes answered the questionnaire. There were 52.1% of female participants and 72.9% of urban residents. 23.9% were obese, regular exercise was reported by 27.7%, and no exercise by 17%. There was a statistically significant association between lifestyle practices and gender (P < 0.001), age (P < 0.001), educational level (P = 0.002), marital status (P < 0.001), duration of diabetes (P < 0.001), hypertension (P < 0.001), high-density lipoprotein (P < 0.001), low-density lipoprotein (P < 0.001), and HbA1c level (P < 0.001). Logistic regression analysis showed male gender and education were significantly associated with lifestyle changes. Men were more likely to engage in favorable lifestyle practices than women (P < 0.001), while those with no formal education were less likely to engage in healthy lifestyle (P < 0.001). CONCLUSIONS: Health authorities in Sudan will need to put more efforts into education for promoting self-awareness and good lifestyle practices in the population with diabetes.